Exploring genetic diversity of rice cultivars for the presence of brown planthopper (BPH) resistance genes and development of SNP marker for Bph18. Issue 3 (3rd May 2016) - Ramkumar, Gandhimani; Prahalada, G. D.; Hechanova, Sherry Lou; Kim, Sung‐Ryul; Jena, Kshirod K.
Abstract: Brown planthopper (BPH) is the most devastating insect pest in rice‐growing areas. Information on availability of BPH resistance alleles and their sources enhances BPH‐resistant breeding programmes. In this study, 260 highly diversified rice cultivars or breeding lines were screened for the presence of five major BPH resistance genes ( Bph10, Bph13, Bph18, Bph20 and Bph21 ) using gene‐specific markers. The analysis revealed that 137 of the 260 cultivars possess at least one BPH resistance gene. Bph10 was predominant while Bph20 was the least distributed. Moreover, two and three different resistance gene combinations were found in the cultivars. Molecular markers play an important role in molecular breeding programmes. A tightly linked PCR‐based co‐dominant Bph18 marker was developed, which is cost effective and time effective and simpler than available Bph18 CAPS marker (7312.T4A). We strongly believe that the identified BPH‐resistant cultivars can be used as alternative resistance gene sources and also as resource for novel BPH resistance genes. The developed Bph18 marker will be highly useful in molecular breeding applications of BPH‐resistant breeding programmes.